2011
DOI: 10.1002/ptr.3365
|View full text |Cite
|
Sign up to set email alerts
|

Antiarthritic Activity of a Standardized, Multiherbal, Ayurvedic Formulation containing Boswellia serrata: In Vitro Studies on Knee Cartilage from Osteoarthritis Patients

Abstract: A validated in vitro model of cartilage damage and published data were used showing that this model measures the chondroprotective and antiinflammatory effects of different antiarthritic drugs. In this report, this model was used to evaluate the effects of a new antiarthritic Ayurvedic formulation containing Zingiber officinale root, Tinospora cordifolia stem, Phyllanthus emblica fruit and oleoresin of Boswellia serrata. Glucosamine sulphate was used as a positive control in the study. Aqueous extracts of each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 29 publications
(32 reference statements)
0
17
0
Order By: Relevance
“…In this context, Panahi et al () have shown that curcuminoids significantly reduce WOMAC, VAS, and Lequesne's pain functional index scores and concluded that curcuminoids also represent an effective and safe alternative treatment for OA. Earlier studies using knee cartilage at in vitro conditions demonstrated the anti‐arthritic effects of an Ayurvedic formulation containing Zingiber officinale root, Tinospora cordifolia stem, Phyllanthus emblica fruit, and oleoresin of B. serrata (Sumantran et al, ). Specifically, oleoresin of B. serrata was shown to play a crucial role in the chondroprotective and anti‐inflammatory activity in OA patients (Sumantran et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, Panahi et al () have shown that curcuminoids significantly reduce WOMAC, VAS, and Lequesne's pain functional index scores and concluded that curcuminoids also represent an effective and safe alternative treatment for OA. Earlier studies using knee cartilage at in vitro conditions demonstrated the anti‐arthritic effects of an Ayurvedic formulation containing Zingiber officinale root, Tinospora cordifolia stem, Phyllanthus emblica fruit, and oleoresin of B. serrata (Sumantran et al, ). Specifically, oleoresin of B. serrata was shown to play a crucial role in the chondroprotective and anti‐inflammatory activity in OA patients (Sumantran et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies using knee cartilage at in vitro conditions demonstrated the anti‐arthritic effects of an Ayurvedic formulation containing Zingiber officinale root, Tinospora cordifolia stem, Phyllanthus emblica fruit, and oleoresin of B. serrata (Sumantran et al, ). Specifically, oleoresin of B. serrata was shown to play a crucial role in the chondroprotective and anti‐inflammatory activity in OA patients (Sumantran et al, ). An earlier study using a triterpene‐rich extract of Vitellaria paradoxa against OA showed a decrease in tumor necrosis factor alpha and a cartilage degradation marker CTX‐II (Cheras, Myers, Paul‐Brent, Outerbridge, & Nielsen, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A BS preparation enriched in active principles was able to hinder cartilage breakdown by metalloproteinase-3 (MMP-3) and to block Intercellular Adhesion Molecule 1 (ICAM-1) and thereby the inflammatory reaction [21]. In another study a B. frereana preparation decreased the synthesis/ activation of several inflammation-related mediators and enzymes (MMP-9 and MMP-13, cycloxygenase-2, nitric oxide, prostaglandin E2), thus thwarting collagen and cartilage dissolution [22].A poly-herbal formulation containing Zingiber officinale root, Tinospora cordifolia stem, Phyllanthus emblica fruit and oleoresin of BS has been shown to halt cartilage degradation in the knee (decreased release of glycosaminoglycans and aggrecan) associated with antiinflammatory activity (as assessed by lower levels of nitric oxide) [23]. Another combination including three herbs (Uncaria tomentosa, Boswellia spp., Lepidium meyenii) and an aminoacid (L-leucine) has been shown to hamper inflammation and protect the articular cartilage.…”
Section: Boswellia Spp Fam Burseraceaementioning
confidence: 99%
“…Chondroitin sulfate was used as a standard [3]. The GAG levels were expressed as microgram equivalents of chondroitin sulfate per milliliter of SF.…”
Section: Case Presentationmentioning
confidence: 99%